A criterion for DT gas thermonuclear ignition by a focusing spherical shock wave - Aleksandrova, A.G.; Popov, N.A.; Shcherbakov, V.A. (Вопросы атомной науки и техники, 2003)
Conditions for thermonuclear ignition of deuterium-tritium (DT) gas by a focusing ideally symmetric shock wave are estimated. The wave is focused to the center and then reflects. In so doing a higher-pressure zone is produced following the front of the shock wave reflected from the center; if the wave is intensive enough, the DT gas thermonuclear ignition can occur in the zone. The ignition criterion can be written as ρ₀r₀u₀²² ≥1, where ρ₀ is initial DT gas density, [ρ₀] = g/cm³, u₀ is mass velocity following the converging shock wave front of radius r₀, [r₀] = cm, [u₀] = 10⁷ cm/sec. Зроблено оцінку умов термоядерного запалювання дейтерій-тритієвого (ДТ) газу сфокусованою ідеально симетричною ударною хвилею. Хвиля фокусується в центрі і потім відбивається назад. Таким способом створюється зона високого тиску, що супроводить фронт відбитої від центра ударної хвилі. Якщо хвиля достатньо інтенсивна, в цій зоні може відбутися термоядерне запалювання ДТ-газу. Критерій такого запалювання може бути записано як ρ₀r₀u₀²² ≥1, де ρ₀ - густина початкового ДТ-газу, г/cм³; u₀ - швидкість маси, яка іде за фронтом ударної хвилі, що сходиться, в радіусі r₀, [r₀] = cм, [u₀] = 10⁷ см/с. Оценены условия термоядерного поджигания дейтерий-тритиевого (ДТ) газа сфокусированной идеально симметричной ударной волной. Волна фокусируется в центре и затем отражается. Таким способом образуется зона высокого давления, следующая за фронтом ударной волны, отраженной от центра. Если волна достаточно интенсивна, в этой зоне может произойти термоядерное поджигание ДТ-газа. Критерий такого поджигания может быть записан как ρ₀r₀u₀²² ≥1, где ρ₀ - плотность начального ДТ-газа, г/cм³; u₀ - скорость массы, следующей за фронтом ударной сходящейся волны в радиусе r₀, [r₀] = cm, [u₀] = 10⁷см/с